VD_FINDINFO Arrêt / 2011 / 332 vom 15. März 2011 - VD Tribunal cantonal (2011)
ADMISSION DE LA DEMANDE, SOUPÇON, ACTE D'ORDRE SEXUEL AVEC UN ENFANT, VISITE, PROVISOIRE | 273 CC, 420 al. 2 CC, 489 CPC, 174 al. 2 CDPJ